Pyridoxine (vitamin B6) - Fairweather-Tait, Susan (Henry Stewart Talks, 2026)
Functions of vitamin B6 in the body, Food sources of vitamin B6, Absorption and metabolism, Biomarkers of intake and status, Deficiency and excess of vitamin B6, Dietary reference values for vitamin B6 for adults